2007
DOI: 10.1113/jphysiol.2007.140624
|View full text |Cite
|
Sign up to set email alerts
|

Increased secretory capacity of mouse adrenal chromaffin cells by chronic intermittent hypoxia: involvement of protein kinase C

Abstract: Previous studies have shown that catecholamine secretion from the adrenal medulla plays a critical role in chronic intermittent hypoxia (CIH)-induced alterations in cardiovascular function. In the present study we examined the cellular mechanisms associated with the effects of CIH on adrenal chromaffin cell catecholamine secretion. Experiments were performed on adult male mice (C57/BL6) that were exposed to 1-4 days of CIH or to normoxia. Perforated patch electrical capacitance recordings were performed on fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
30
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
3

Relationship

5
3

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 22 publications
4
30
0
Order By: Relevance
“…Simulating recurrent apnea by exposing rodents to intermittent hypoxia produces an imbalance in HIF-α isoforms manifested by increased HIF-1α (30) and decreased HIF-2α (18) protein levels in the CB and AM. Intermittent hypoxia-exposed rodents exhibit oxidative stress, increased Nox2 and decreased Sod2 levels, augmented hypoxic responses by the CB and AM, hypertension, and breathing abnormalities (30)(31)(32), which recapitulate the phenotype of Hif-2α +/− mice. Remarkably, either blockade of changes in HIF-α isoforms or normalization of the intracellular redox state by antioxidants reverses the effects of intermittent hypoxia in rodents (18,(29)(30)(31)(32)(33).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Simulating recurrent apnea by exposing rodents to intermittent hypoxia produces an imbalance in HIF-α isoforms manifested by increased HIF-1α (30) and decreased HIF-2α (18) protein levels in the CB and AM. Intermittent hypoxia-exposed rodents exhibit oxidative stress, increased Nox2 and decreased Sod2 levels, augmented hypoxic responses by the CB and AM, hypertension, and breathing abnormalities (30)(31)(32), which recapitulate the phenotype of Hif-2α +/− mice. Remarkably, either blockade of changes in HIF-α isoforms or normalization of the intracellular redox state by antioxidants reverses the effects of intermittent hypoxia in rodents (18,(29)(30)(31)(32)(33).…”
Section: Discussionmentioning
confidence: 94%
“…Intermittent hypoxia-exposed rodents exhibit oxidative stress, increased Nox2 and decreased Sod2 levels, augmented hypoxic responses by the CB and AM, hypertension, and breathing abnormalities (30)(31)(32), which recapitulate the phenotype of Hif-2α +/− mice. Remarkably, either blockade of changes in HIF-α isoforms or normalization of the intracellular redox state by antioxidants reverses the effects of intermittent hypoxia in rodents (18,(29)(30)(31)(32)(33). Thus, correcting the changes in intracellular redox state by selective modulation of either HIF-1α or HIF-2α expression may represent a unique therapeutic approach for the treatment of cardio-respiratory abnormalities caused by sleep disordered breathing with apnea.…”
Section: Discussionmentioning
confidence: 94%
“…Alternatively, chronic intermittent hypoxia attenuates baroreflex function, which might abrogate the normal inhibition of sympathetic activity by arterial baroreflex [20]. Hypoxia in animal models also directly affects chromaffin cells of the adrenal medulla, promoting increased secretion of catecholamines [21] as well as stimulating the expression of enzymes for catecholamine synthesis such as tyrosine hydroxylase, dopamine beta hydroxylase, and phenylethanolamine-N-methyltransferase [22,23] (Fig. 1).…”
Section: The Effect Of Hypoxia On Catecholaminesmentioning
confidence: 99%
“…Still other work has shown that PKC activation can occur in a Ca 2+ -mediated manner in response to repetitive cell stimulation [20]. Subsequent reports have shown that the PKC-sensitive step in RRP augmentation is likely the phosphorylation of the SNARE protein SNAP-25 [38], and that PKC-mediated augmentation is a key component of increased adrenal output under native hypoxic stress in whole animals [3, 39]. Lastly, in a parallel signaling path, adrenal chromaffin cells have been shown to be highly sensitive to splanchnic release of the potent peptide secretagogue, PACAP [33, 40, 41].…”
Section: Discussionmentioning
confidence: 99%